Volterra and Functional Differential Equations - Hannsgen, Kenneth B. (CRC Press, 2017)
This book contains twenty four papers, presented at the conference on Volterra and Functional Differential Equations held in Virginia in 1981, on various topics, including Liapunov stability, Volterra equations, integral equations, and functional differential equations.